Investment climate of Georgia - Faruk Gürsoy; Olcay Kurşun (IBSU Scientific Journal (IBSUSJ), 2008)
This study tries to present the current picture of investment climate of Georgia. This work, we believe, will also fill the knowledge gap in the area of foreign direct investment (FDI) research on Georgia. The analysis focuses on major obstacles faced by investors. We first identify and then quantify the major obstacles for both foreign and domestic investors using the case studies of investors in Georgia and the statistics obtained from these data. The study results indicates that the most serious problem for investors is the human factor, which comprises of corruption and unskilled local labor force. We also found that the issues such as government regulations (regulatory burden), infrastructure, or safety do not act as major deterrents of FDI inflows, especially after the successful reforms of the Saakashvili government. It was also found that most investors have been satisfied with their operation.
Keywords: 330; Foreign Direct Investment; Investment Climate; Georgia